Endovascular therapy versus best medical care for acute ischemic stroke with distal medium vessel occlusion: a systematic review and meta-analysis - Ziyue Wang; Jiacheng Li; Qianqian Kong; Hao Yan; Yi Zhang; Xirui Zhou; Zhiyuan Yu; Hao Huang; Xiang Luo (Annals of Medicine)
Background With the refinement of catheter technology, distal medium vessel occlusions (DMVOs) are now viewed as amenable to endovascular treatment (EVT) but its efficacy and safety remains unclear in AIS patients with DMVO.Methods We conducted a systematic search of PubMed, Embase databases and Cochrane Library up to December 2023 using keywords to identify studies comparing EVT versus BMT in AIS with DMVOs. The assessed clinical outcomes were excellent functional outcome, good functional outcome, 90-day mortality, symptomatic intracranial hemorrhage (sICH), and early neurological improvement (ENI) after treatment.Results Overall, 31 studies were included. There were no significant differences in excellent functional outcome (OR: 1.21, 95% CI: 0.99-1.47), good functional outcome (OR: 1.03, 95% CI: 0.82-1.30) and 90-day mortality (OR: 1.17, 95% CI: 0.84-1.62). Additionally, EVT led to higher sICH (OR: 1.64, 95% CI: 1.09-2.47) and better ENI (OR: 1.50, 95% CI: 1.02-2.19) compared to BMT. In individuals with M2 occlusion receiving EVT showed better excellent functional outcomes (OR: 1.48, 95% CI: 1.07-2.03). Those patients with PCA occlusion showed no significant difference in functional outcomes. In individuals with ACA occlusion, EVT resulted in reduced functional independence (OR: 0.55, 95% CI: 0.31-0.98). For NIHSS < 6, BMT achieved better functional independence compared to EVT (OR: 0.71, 95% CI: 0.51-0.98) and EVT showed higher sICH (OR: 3.44, 95% CI: 1.42-8.31).Conclusion For patients with AIS and DMVO occlusion, EVT fails to improve functional prognosis while increasing sICH incidence. More randomized controlled trials are needed in the future to confirm these results.